THE IMPLEMENTATION OF CLINICAL SUPERVISION IN IMPROVING THE QUALITY OF LEARNING AT AL-BAHJAH - Lili Gozali; Mumun Munawaroh (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
During the pandemic covid-19 era, teachers felt difficulties in adjusting their learning activities. This study aims to determine the implementation of clinical supervision in improving the quality of learning at SDIQu Al-Bahjah during the pandemic. Through a descriptive qualitative research approach, it was found that implementing clinical management at SDIQu Al-Bahjah during the pandemic was almost the same as implementing it in standard times. What distinguishes it is the findings. In the observation process, it was found that there was a mismatch between the agreed criteria and the learning actions carried out by the teacher. In the first cycle, the majority of teachers felt less prepared in terms of facilities in teaching. Of the 20 teachers, 18 people have not mastered online learning techniques, 12 people have not compiled the learning media needed during the pandemic. In the next cycle, there was significant progress. Almost all teachers had facilitated their learning needs. They can apply online learning with the media used. In the following process, observation is focused on maximizing the learning media on the learning functions that can be achieved. After several clinical supervision cycles, teachers successfully solved their learning problems and were more motivated to improve their professional competence continuously.